THE TRANSLATION STRATEGY OF IMPERATIVE SPEECH ACT IN FOLKOLORE BILINGUAL BOOK LITTLE SUNSHINE - Sihotang, Christian Jonatan Anggiat Daulat; Sipayung, Kammer Tuahman; Silitonga, Harpen (Jurnal Review Pendidikan dan Pengajaran, 2024)
Imperative Speech Act is utterances that state a relationship or link between two parties because of the action between the speaker and the listener so that the speaker asks the listener to act. Translation Strategy is it is a framework that aims to understand and analyze the decision-making process of translators when they choose a particular translation strategy to convey meaning across different languages and cultures.This study aims to know some direct utterance imperative speech actsin the Folklore bilingual book and to know the translation strategy used in translating the translation. This study uses a descriptive qualitative method. the researcher applied the translation strategy-based theory of Moentaha (2008). The results show that there are 21 direct imperative utterances found. In addition to that, there are eight translation strategies found in the folklore, they are literal translation 8 data (38%), Substitution 1 data (5%), Free Translation 1 data (5 %), Paraphrasing 2 data (10%), Replacement 4 data (19 %), additions 2 data (10 %), omission 2 data (10%), descriptive Translation Application 1 data (5%). The results of the study have 21 data and 8 translation strategies contained in the Folklore bilingual book.